BEBERAPA SIFAT KIMIA TANAH LAHAN PERKEBUNAN CAMPURAN BEKAS LAHAN PERSAWAHAN DI KELURAHAN PANAU KECAMATAN TAWAELI - Ikhsan, Moh.; Ramlan, Ramlan; Rajamuddin, Ulfiyah A. (AGROTEKBIS, 2018)
The purpose of this research was to observe of soil chemical properties of paddy land which use changed into a mixed plantation at Panau Village Tawaeli District. Soil analysis was carried out at the Laboratory of Soil Science Unit of the Faculty of Agriculture, Tadulako University. The method used in this research is a field survey by reviewing and determining the location of sample observation point on each land use (paddy field and mixed garden) and continued with take the undisturb soil sampling with depth (0-20) cm fromÂ  Top soil using ground drill. In the mixed garden area, samples were taken in 4 different locations and paddy fields in 4 different locations, so that the total number of composite soil samples were 8 samples. The results showed that the changes in soil chemical properties on each land use (paddy fields and mixed garden land) vary widely with slightly acid pH to slightly alkalis. C-Organic high, to very low. N-total is moderate to very low. P-total is high to moderate. K-total is high, to very low. CEC is high, to very low. Differences place cause changes in soil chemical properties.Â Keywords : Soil Chemical Characteristics, Paddy Land And Mixed Garden Lands